A organização e luta das mulheres camponesas dos assentamentos do Oeste/PR para se constituírem como sujeita de direitos:conquistas, contradições e limites - Gubert , Flavia Piccinin Paz (2022)
This thesis aims to analyze the constitution of peasant women settled in the West of Paraná as subjects of social rights, from their organization, highlighting the contradictions, limits and achievements and aims to answer the following research problem: "peasant women from the West Settlements of Paraná are organized as subjects of rights, in search of their social rights?”. Thus, in order to answer the research problem, at first, it seeks to describe the path of subordination of women as subjects of law, passing through the conceptual analysis of the peasantry to peasant feminism, from a context of resistance and confrontation to patriarchal exploitation and capitalist. In the sequence, it is about the social rights that have been impeded, contextualizing these with the field research, in order to understand the peasant woman settled as a subject of rights, from its organization. Thus, the proposed theme aims to study sustainability and development, thinking about the role of women in the rural environment, a factor that justifies adopting the peasant and settled woman as the protagonist. The thesis used the hermeneutic and dialectical method of approach as a path, with the research being analytical and exploratory, within its theoretical and conceptual conception; qualitative and quantitative in terms of how to approach the problem. The empirical foundation was carried out by fieldwork, mainly when semistructured interviews and questionnaires were applied to women from the West Paraná Settlements, since these constitute a territory of resistance and reproduction of peasant relations. In short, it was possible to understand that from the women's organization, whether at the local level, within their associations such as mothers' clubs, cooperatives or together with state militancy and social movements, settled peasant women engage in various processes of struggle for their rights, and from these organizational processes, a collective construction of resistance strategies and coping with local difficulties is born, which make possible the constitution of the settled peasant woman as a subject of social rights.